Critical intersex - Holmes, Morgan (Ashgate, 2009)
To date, intersex studies has not received the scholarly attention it deserves as research in this area has been centred around certain key questions, scholars and geographical regions. Exploring previously neglected territories, this book broadens the scope of intersex studies, whilst adopting perspectives that turn the gaze of the liberal, humanist, scientific outlook upon itself, in order to reconfigure debates about rights, autonomy and subjectivity, and challenges the accepted paradigms of intersex identity politics. Presenting the latest theoretical and empirical research from an international group of experts, this is a truly interdisciplinary volume containing critical approaches from both the humanities and social sciences. With its contributions to sociology, anthropology, medicine, law, history, cultural studies, psychology and psychoanalysis, Critical Intersex will appeal to scholars and clinical practitioners alike.
Section: 1 vol. (XIV-257 p.) ; 24 cm.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; inégalités; premier cycle; queer; santé; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; violences; violences médicales; études intersexes

Évaluation d’une intervention de groupe d’approche féministe auprès de femmes victimes d’agression sexuelle - Bergeron, Manon; Hébert, Martine (Child abuse & neglect, 2006)
The present study evaluates a group intervention using a feminist approach for women experiencing sexual abuse in childhood or adulthood in order to measure changes associated with participation in a group intervention and verifies whether effects are maintained over time. The present study relates effects of the group intervention in terms of psychological distress, depression symptoms, post-traumatic stress symptoms and feelings of guilt and helplessness.The sample consists of 26 women participating in a group intervention offered by sexual assault centers in Quebec (CALACS - Centre d'aide et de lutte contre les agressions à caractère sexuel).Results show significant differences between pretest and post-test scores obtained one week following the end of the group intervention and gains are maintained at follow-up 3 months later. The findings suggest that participation in the group intervention is associated with a reduction of psychological distress, depression symptoms, post-traumatic stress symptoms and feelings of guilt and helplessness in adult women reporting sexual abuse.
Keywords: discipline; outils; recherche en milieux de pratique; ressource en ligne; sciences humaines; sexologie; thématiques; violences; violences contre les femmes*; violences sexuelles

Les pratiques traditionnelles affectant la santé physique et mentale des femmes; l'excision et l'infibulation - situation actuelle et perspectives d'avenir - Vissandjée, B.; Ndejuru, R.; Kantiébo, M.; Renaud, J.; Aïthachimi, L.; Levine, L.; Lapointe, M. (Institut universitaire SHERPA, 2001)
L’excision et l’infibulation sont parties intégrantes des traditions de nombreuses sociétés africaines issues majoritairement de la région subsaharienne. En contexte canadien, aucune information statistique n’est présentement disponible sur la prédominance de cette pratique, malgré le fait que de nombreux intervenants soupçonnent que plusieurs immigrant(e)s en provenance de ces pays sont susceptibles de faire subir ces pratiques à leurs fillettes. Cette étude qualitative explore les valeurs et les croyances des immigrant(e)s par rapport à ces pratiques traditionnelles, tout en cernant les défis de leur processus d’intégration au Canada et leur recours aux services de santé.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; corps; cours; discipline; interculturalité; migration; médecine; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences; sciences humaines; sciences infirmières; sex2283; sexologie; sexualité; thématiques; violences